2006
DOI: 10.1021/jf060533c
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Modality of Texture and Aroma Perception Is Independent of Orthonasal or Retronasal Stimulation

Abstract: To assess the influence of orthonasal and retronasal stimulation on cross-modal interactions between texture and flavor perception of food, a series of experiments have been conducted. Healthy human subjects were exposed to strawberry aroma pulses delivered by a computer-controlled stimulator based on air dilution olfactometry. Just prior to exposure to the aroma, the human subjects consumed water, custard, or protein gels with different textures without any added aroma. The aroma was delivered as a sequence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…-During oral processing of foods and swallowing, the senses involved interact in a nonlinear way meaning that texture and taste influence the perception of odors (e.g., [31 -33]). Results obtained by Visschers et al [34] suggest that the intensity of aroma decreased with increasing consistency of the consumed food. In addition, it has been shown that retronasal odorous stimuli increase the intensities of thickness and creaminess of oral stimuli [35].…”
Section: Interactions Orthonasal and Retronasal Odorous Stimuli And Tmentioning
confidence: 90%
“…-During oral processing of foods and swallowing, the senses involved interact in a nonlinear way meaning that texture and taste influence the perception of odors (e.g., [31 -33]). Results obtained by Visschers et al [34] suggest that the intensity of aroma decreased with increasing consistency of the consumed food. In addition, it has been shown that retronasal odorous stimuli increase the intensities of thickness and creaminess of oral stimuli [35].…”
Section: Interactions Orthonasal and Retronasal Odorous Stimuli And Tmentioning
confidence: 90%
“…It was demonstrated that indeed the aroma profile that was generated with the olfactometer closely resembles the concentration of volatiles in the nose space measured for an individual subject eating or drinking a specific product. This enables the design of complete aroma release profiles that mimic those obtained by in vivo experiments during the consumption of foods (28) . Fig.…”
Section: Aroma Stimulationmentioning
confidence: 99%
“…Thus, when presented through the mouth, retronasal stimuli are typically accompanied by other stimulation, such as taste, texture, or temperature, which may interact with olfactory perception (Cerf-Ducastel and Murphy 2001;Small et al 1997;Small and Prescott 2005;Visschers et al 2006). As we wanted to investigate hedonic differences between orthonasal olfaction and retronasal olfaction, we had to be certain that the overall sensory input was the same between conditions.…”
Section: Introductionmentioning
confidence: 99%